Effectiveness Test of Immobilization of Aspergillus niger Fungi with Different Biomass on Hexavalent Chromium (Cr VI) in Water - Anisa Fitriawati; Ima Yudha Perwira; Devi Ulinuha (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
Heavy metal contamination with Cr(VI) in aquatic environments is a serious concern due to its high toxicity and mobility. This research aimed to evaluate the effectiveness of immobilized Aspergillus niger in sodium alginate with different biomass concentrations (0 g, 0.1 g, 0.3 g, and 0.5 g) in reducing Cr(VI) content in water. The research was conducted from March to May 2025 using a quantitative experimental method with a Completely Randomized Design (RAL), consisting of four treatments and three replications. The bioremediation process lasted 5 days, and Cr(VI) concentration was measured using a UV-Vis spectrophotometer at 540 nm, with the data analyzed in Microsoft Excel. The results indicated that each biomass treatment exhibited varying levels of Cr(VI) removal. The treatments T3, T1, T2, and T0 (control) showed the highest to lowest effectiveness, with values of 39.4%, 32.4%, 30.7%, and 28.0%, respectively. The rate of Cr(VI) reduction increased with increasing fungal biomass, but not in a straight line across all treatments. The metal removal process occurred through biosorption and bioaccumulation mechanisms, influenced by factors such as initial metal concentration, particle size, and the availability of functional groups on the fungal cell wall and alginate matrix. This study demonstrates that immobilized Aspergillus niger can reduce Cr(VI) content in water, although its effectiveness is not yet optimal.